Serious Game for Training with Cycloergomery Adapted for Hemiparetic Patients Post-Stroke in Hospital Phase: a viability study (Research, Society and Development, 2022)
Cycloergometry associated with a Serious Game can contribute to the improvement of lower limb motor performance, aerobic capacity, balance, and in addition, increase motivation during therapy. This study is conducted to evaluate the feasibility of using adapted cycle ergometry associated with a serious game on hemiparetic patients due to stroke in the acute phase. It is a feasibility study with a quantitative cross-sectional design, with hospitalized patients aged 18 years or older and clinically stable. Pre-intervention: lower limb performance (Sit and Stand Test for five times) and functional mobility (Timed Up and Go Test) evaluated. A Likert scale was applied to verify the motivation, training ease performing, and the participants' perception of the resource’s usefulness. The Serious Game was used on two consecutive days for 30 minutes each. Vital signs and perceived exertion (Borg Scale) were monitored during therapy. Sixty-five individuals, with a mean age of 62, 88 12, 23, participated in the research. Regarding motivation during the game, 98.5% of the participants reported feeling motivated during the activity. The resource was considered easy for 87.7% of the individuals, and 78.5% perceived its usefulness in therapy. There was no statistically significant difference in hemodynamic variables, demonstrating safety in the application of the game in the acute phase. The motivation, attention, engagement, and satisfaction with the usage of the system during the sessions indicate a very interesting potential for use in this phase.